HUBUNGAN SIKAP BELAJAR ONLINE TERHADAP DISABILITAS LOW BACK PAIN MYOGENIK DI SMA NEGERI 5 KAB. TANGERANG: Indonesia - Uga Cahyani; Jerry Maratis; Eko Wibowo (Jurnal Ilmiah Fisioterapi, 2024)
Objective: To determine the relationship between online learning attitudes and the level of myogenic low back pain disability in SMA Negeri 5 Kab. Tangerang. Methods: This research is a correlative analytical research using a cross-sectional design. The total sample was 32 people with an age range of 16-18 years, namely students from SMA Negeri 5 Kab. Tangerang. Online Learning Attitude data was measured using the Rapid Entire Body Assessment (REBA). In contrast, the results of measuring the level of myogenic low back pain disability were measured using the Modified Oswestry Disability Index (MODI). Result: Hypothesis testing with Chi-Square produces a p-value of 0.540 (p>Î± (0.05)). The average and standard deviation of online learning attitudes using the Rapid Entire Body Assessment measurement is 4.72 Â± 1.250, and the level of myogenic low back pain disability using the Modified Oswestry Disability Index measurement is 19.44 Â± 10.922 for students at SMA Negeri 5 Kab. Tangerang. Conclusion: There is no relationship between online learning attitudes and the level of myogenic low back pain disability in SMA Negeri 5 Kab. Tangerang. Keywords: Online Learning Attitude, Low back pain Myogenic Disabilities, Rapid Entire Body Assessment, Modified Oswestry Disability Index.